2007
DOI: 10.1111/j.1572-0241.2007.01437.x
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Nutritional Status Is Predictive of Response to Treatment and Survival in Patients Treated by Definitive Chemoradiotherapy for a Locally Advanced Esophageal Cancer

Abstract: Survival was influenced by baseline nutritional status as well as dysphagia, dose of RT, and CR to CRT. Despite the retrospective design of the study, our results may provide the concept basis for performing a prospective nutritional intervention study in patients treated by definitive CRT for an esophageal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
112
3
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(123 citation statements)
references
References 29 publications
4
112
3
4
Order By: Relevance
“…Undernutrition has been reported to be as frequent as 79% in patients with advanced esophageal cancer before starting treatment (31). In these patients, anorexia and dysphagia are the main factors involved in the onset of undernutrition (32). Basically, limitation of oral intake can be caused by tumor obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Undernutrition has been reported to be as frequent as 79% in patients with advanced esophageal cancer before starting treatment (31). In these patients, anorexia and dysphagia are the main factors involved in the onset of undernutrition (32). Basically, limitation of oral intake can be caused by tumor obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition and inflammation suppress albumin synthesis (Yeun et al, 1998). In an adult the normal range of serum albumin is defined as 3.5-5.0 g/dL and levels <3.5 g/dL is called hypoalbuminemia (Di Fiore et al, 2007;Ishizuka et al, 2007). The inverse correlation between albumin synthesis and body weight index in cancer patients supports the possibility of a compensatory enhanced albumin synthesis in these metabolically affected patients.…”
Section: Discussionmentioning
confidence: 99%
“…A few reports that specifically focused on BMI suggested that pretreatment BMI was not associated with differential outcome with regard to OS or DFS. [12][13][14] However, the largest study to date is by Trivers et al 17 18 demonstrated that a BMI of >18 kg/m 2 was one of the independent prognostic factors in 105 patients treated with definitive chemoradiotherapy (P ¼ .003). However, in this study, the cutpoint for BMI was nontraditional and the sample size was small.…”
Section: Discussionmentioning
confidence: 99%